Surgical Management of Ebsteins Anomaly with Atrial Septal Defect in a Young Lady: A Case Report - Rahman, CM Mosabber; Alam, SM Rakibul; Sunny, Samir Azam; Adhikary, Asit Baran (University Heart Journal, 2017)
Ebsteins anomaly is a rare congenital heart defect accounting for <1% of all cases. It is commonly associated with other cardiac malformations particularly, 50% of the patients are associated with atrial septal defect. We report a 22-year-old lady diagnosed to have Ebsteins anomaly with small atrial septal defect. She was surgically managed in Bangabandhu Sheikh Mujib Medical University by replacing the defective tricuspid valve withSt Jude Medical Epic porcine bio-prosthetic heart valve along with plication of atrialized portion of right ventricle and direct closure of the atrial septal defect.This resulted in excellent symptomatic improvement. University Heart Journal Vol. 12, No. 1, January 2016; 37-39